2012
DOI: 10.1021/jp306640z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Pristine and Alkali Metal Doped Picene Layers: Confirmation of the Insulating Phase in Multilayer Doped Compounds

Abstract: The electronic structure and the geometric arrangement of picene molecules adsorbed on Ag(111) were studied by means of photoemission and near-edge X-ray absorption fine-structure spectroscopies (NEXAFS). While the valence band of a picene monolayer shows a clear metallic state that evolves with alkali metal doping, in the case of a picene multilayer there is no evidence of metallic states evolving with doping. Our data suggest that the bulk ultrahigh-vacuum films of K x picene are in an insulating phase, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
34
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 34 publications
(85 reference statements)
7
34
1
Order By: Relevance
“…This representation nicely shows the evolution of in-gap spectral weight upon doping, with none of the spectra displaying any metallic Fermi edge. The observation that even the x = 3 phase, for which superconductivity has been claimed, remains gapped is most surprising, but in agreement with two previous reports [24,25]. As one possible explanation polaronic effects have been suggested [24], which may cause a pseudogap at the Fermi level as has been observed, e.g., in oxides [37].…”
supporting
confidence: 88%
See 1 more Smart Citation
“…This representation nicely shows the evolution of in-gap spectral weight upon doping, with none of the spectra displaying any metallic Fermi edge. The observation that even the x = 3 phase, for which superconductivity has been claimed, remains gapped is most surprising, but in agreement with two previous reports [24,25]. As one possible explanation polaronic effects have been suggested [24], which may cause a pseudogap at the Fermi level as has been observed, e.g., in oxides [37].…”
supporting
confidence: 88%
“…In fact, the importance of electron-electron correlations in K 3 picene was pointed out by Giovannetti et al [21] and Kim et al [22] who found an insulating state with antiferromagnetic order from ab initio calculations. Experimentally, the picture of the electronic structure has remained controversial: while one photoemission study reported the appearance of metallic spectral weight at the Fermi level for x = 1 [23], other authors [24,25] failed to observe a metallic Fermi edge for a wide concentration range from x = 0.22 to 3.6 and speculated about the possible role of correlations and polaronic effects [24].…”
mentioning
confidence: 99%
“…The Photoemission spectroscopy (PES) reported by Okazaki et al showed metallic behavior in thin films of K-doped picene [21,22], i.e., the PES peak was observed at the Fermi energy with K-doping of picene thin films and the peak disappeared with excess K-doping. However, the PES reported by other groups showed no metallic behavior [23][24][25]. Okazaki et al suggested that the observation of metallic behavior originated in the different crystal structures of picene thin-films, which change depending on the substrates used.…”
Section: Superconductivity and Features Of Metal-doped Picene Solidsmentioning
confidence: 97%
“…[38][39][40][41][42] Most importantly, various photoelectron spectroscopy studies revealed that thin films of potassium-intercalated picene show a negligible density of states at the Fermi level which has been explained by such correlations effects. [40][41][42] It therefore seems to be quite likely that also for Cadoped picene the electronic correlations are strong enough to localize the charge carriers and to lead to a nonmetallic ground state. Moreover, the fact that there is hybridization between Ca and picene derived states in Ca-doped picene (see previous discussion) demonstrates that a rigid bandlike behavior upon intercalation and associated charge transfer certainly is not appropriate to describe this compound.…”
Section: -28mentioning
confidence: 99%